2016
DOI: 10.1038/srep21541
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of microscopically positive margins for primary gastrointestinal stromal tumors: a systematic review and meta-analysis

Abstract: The impact and management of microscopically positive margins in gastrointestinal stromal tumors (GISTs) remain unclear. The aim of this study is to estimate the prognostic value of surgical margins for disease-free survival (DFS) and overall survival (OS) in patients with primary GISTs. Twelve studies with 1985 GIST patients were included. The overall recurrence rate in R1 resection and R0 resection group was 0.364 (95% CI 0.299–0.429) and 0.296 (95% CI 0.161–0.430), respectively. Meta-analysis confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…Although individual studies imply an advantage in terms of local recurrence-free survival for resection margins larger than 1 cm, marginal resections are considered appropriate as long as microscopically tumor-free margins are established [14,15]. In contrast to gastrointestinal carcinomas, systematic lymphadenectomy is not indicated in GIST since lymph node metastases are a rare event.…”
Section: Principles Of Surgery and Different Rationales For Preoperatmentioning
confidence: 99%
“…Although individual studies imply an advantage in terms of local recurrence-free survival for resection margins larger than 1 cm, marginal resections are considered appropriate as long as microscopically tumor-free margins are established [14,15]. In contrast to gastrointestinal carcinomas, systematic lymphadenectomy is not indicated in GIST since lymph node metastases are a rare event.…”
Section: Principles Of Surgery and Different Rationales For Preoperatmentioning
confidence: 99%
“…It seems that this strategy could attenuate the risk of recurrence for primary GIST after R1 resection. The results of a meta-analysis indicated that adjuvant imatinib therapy can decrease the risk of recurrence in primary GIST after R1 resection (HR 1.3), and in the group of patients after R1 resection without adjuvant therapy disease-free survival remained poorer [36]. Nevertheless, according to the analysis of databases of two adjuvant trials, i.e.…”
Section: Influence Of Perioperative Therapymentioning
confidence: 99%
“…Crosby et al [35] reported that in 10 out of 24 patients with negative microscopic margins in primary resection of small bowel GIST and negative lateral margins, peritoneal metastases were detected, which may support this theory. In a systematic review and meta-analysis evaluating the prognostic role of microscopically positive margins for primary GIST [36], which was based on 12 studies comprising 1,985 patients, it was concluded that a microscopically positive margin may have significant impact on disease-free survival (HR (hazard ratio) 1.6; p = 0.09) without influence on overall survival (HR 1.4).…”
Section: Margins and Risk Of Recurrencementioning
confidence: 99%
“…Successful diagnosis of small pre-malignant lesions and early-stage tumors can significantly benefit cancer treatment and improve the survival rate for patients 17 . In the past few decades, there have been numerous advances in fluorescence-based imaging tools for clinical diagnosis, surgical guidance, and therapeutic applications 813 .…”
mentioning
confidence: 99%